STRATEGI PENGEMBANGAN AGROINDUSTRI SERAT SABUT KELAPA BERKARET (SEBUTRET) (Studi Kasus di Kabupaten Sambas) - JUNARDI, JUNARDI; SUKARDI, SUKARDI; ARKEMAN, YANDRA; ANDIYONO, ANDIYONO (Jurnal Social Economic of Agriculture, 2017)
The combination ofcoconutcoirandrubbercan produce rubberized coir products(sebutret). The sebutret is verypotential to be developedto gain value added and increase farmers and local government incomes. The research objectiveswere to assessinternal and external factorsthat affect theproduct development and the implicationofstrengths,weaknesses, opportunities, and threats. The data obtained were analyzed descriptively and quantitatively in the form of weighted average scores and analysis strategies with SWOT analysis matrix, IFE, EFE and IE. The studyshowsthat the main strength is the availability of sebutret product market and its main weakness is thelow competitiveness, limited scope of local villages and districts. Meanwhile the main opportunity is sebutret manufacturing technology already exists and the main threat is the absence of a strong business partnership. The analysisshows thedevelopment of sebutret agro industry can be managedwith market penetration strategy and product development. Implication of the analysis is formulated alternative strategy, namely: conduct accurate data collection, conduct a feasibility study, produce sebutret accordance with market demand, conduct the preparation of resources, establish processing industries, cooperate with the competent institutions, provide equipment and machinery, provide expert as facilitators, conduct promotion.